2005
DOI: 10.1055/s-2005-867090
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nonreassuring Fetal Heart Rate Patterns and Subsequent Cerebral Palsy in Pregnancies with Intrauterine Bacterial Infection

Abstract: We evaluated an association of nonreassuring fetal heart rate (FHR) patterns and subsequent cerebral palsy (CP) in pregnancies with intrauterine bacterial infection. Among 10,030 infants born during 1995 to 2000, 139 were complicated with acute intrauterine bacterial infection in labor. The FHR patterns 2 hours immediately before delivery were interpreted according to the guidelines of the National Institute of Child Health and Human Development. The correlations between the FHR patterns and umbilical blood ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 13 publications
1
24
0
2
Order By: Relevance
“…Current electronic FHR monitoring technology is not designed to detect FSIRS. In one study, tachycardic fetuses with infection had an increased risk of encephalopathy and cerebral palsy, but had no acidaemia or bradycardia, 54 suggesting that infection may exert neurological injury directly or via a non-hypoxia pathway. Further still, fetal inflammation and hypoxia appear to act synergistically to increase the risk of encephalopathy and cerebral palsy exponentially.…”
Section: 48mentioning
confidence: 99%
“…Current electronic FHR monitoring technology is not designed to detect FSIRS. In one study, tachycardic fetuses with infection had an increased risk of encephalopathy and cerebral palsy, but had no acidaemia or bradycardia, 54 suggesting that infection may exert neurological injury directly or via a non-hypoxia pathway. Further still, fetal inflammation and hypoxia appear to act synergistically to increase the risk of encephalopathy and cerebral palsy exponentially.…”
Section: 48mentioning
confidence: 99%
“…Third, all evaluation items of the FHR pattern were categorical variables. The absence or decrease of variability is thought to represent a state of fetal acidosis (Siira et al 2013), and we focused on decreased variability as reported in other studies (Salafia et al 1998;Sameshima et al 2005 induced by lipopolysaccharides (LPS) was associated with a transient increase in FHR variability and loss of FHR variability by repeated exposure to LPS (Lear et al 2014), so rigorous FHR evaluation including increased variability might be required in future studies focused on the evaluation of intrauterine infection. Furthermore, in certain cases, variability is not determined quantitatively but judged subjectively based on the recorded data, and, thus, quantitative analysis in observational study might be also required.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study did not show any association between histological CAM and abnormal FHR patterns indicative of a hypoxic state or acidemia. A previous study reported that FHR deceleration was not associated with intra-amniotic infection in patients who subsequently developed cerebral palsy (Sameshima et al 2005). An observational study also reported that intrauterine histological CAM is not associated with fetal acidosis (Holcroft et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asphyxie foetale progressive au cours du travail selon le modèle dit de Hon avec des ralentissements tardifs, montrant l'association des ralentissements de type hypoxique (tardifs) à une tachycardie progressive et à une perte d'oscillations en cas d'acidose manifeste (tracé B au cours d'une grossesse prolongée avec un pH AO à 7,04), alors que le tracé A manifeste une hypoxie débutante (pH AO à 7,21). développer une atteinte de la substance blanche, même si la perte de variabilité et les décélérations restent des témoins de l'acidose métabolique, ce qui suggère un mécanisme physiopathologique différent d'une hypoxie-ischémie, d'autant plus que l'IMOC apparaît fréquemment associée au faible âge gestationnel et à la tachycardie témoignant d'infection intra-utérine [89][90][91].…”
Section: Rythme Cardiaque Foetal Et Imocunclassified